The Influence of Creative Accounting and Tax Planning on Financial Performance with Corporate Social Responsibility as a Moderating Variable in the Tourism Industry in Indonesia - Prameswari, I Gusti Agung Istri Pradnya; Adiputra, I Made Pradana; Sinarwati, Ni Kadek (Dinasti Publisher, 2025)
This study aims to investigate the impact of creative accounting and tax planning on financial performance, with Corporate Social Responsibility (CSR) as a moderating variable, in tourism sector companies listed on the Indonesia Stock Exchange during 2022–2024. The research applies a quantitative approach using multiple linear regression and Moderated Regression Analysis (MRA). Data were obtained from annual and sustainability reports of companies selected through purposive sampling, resulting in a total of 105 observations from 35 companies over three years. The findings reveal that creative accounting has a significant positive effect on financial performance, while tax planning shows a significant negative effect, particularly when carried out aggressively, which may harm the company. Moreover, Corporate Social Responsibility (CSR) strengthens the positive effect of creative accounting and weakens the negative effect of tax planning on financial performance by enhancing transparency, accountability, and stakeholder trust.